The Influence Of Work Environment, Motivation and Style Leadership Towards Employee Productivity in PT. Telkom Indonesia Jakarta - Andini Septiani; Muhammad Junaid Kamaruddin (MJK PUBLISHER, 2026)
The focus of this study is to distinguish how the work environment, work motivation, and leadership style affect the productivity of call center employees at PT Telkom Indonesia (Jakarta). Through a quantitative descriptive approach, this study involved 92 respondents as a sample from a total population of 120 employees using the Slovin formula. Primary data collected from Likert-sized questionnaires were then processed using IBM SPSS Statistics 29, including validation tests, reliability, multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study indicate that, partially, the work environment has a positive and significant effect on employee productivity with a calculated value of 3.125 and a significance of 0.002. Work motivation has a positive and significant effect with a calculated t-value of 4.268 and a significance of 0.000. Leadership style has a positive and significant effect with a calculated t-value of 2.894 and a significance of 0.005. Simultaneously, the work environment, work motivation, and leadership style have a significant effect on employee productivity with a calculated F-value of 42.781 and a significance of 0.000. The adjusted Rsquared value of 0.579 indicates that the independent variable is able to explain employee productivity by 57.9%.